Proceedings of the 29th International Symposium on High-Performance Parallel and Distributed Computing 2020
DOI: 10.1145/3369583.3392675
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-scale VM-deflation for Running Interactive Applications On Transient Servers

Abstract: Transient computing has become popular in public cloud environments for running delay-insensitive batch and data processing applications at low cost. Since transient cloud servers can be revoked at any time by the cloud provider, they are considered unsuitable for running interactive application such as web services. In this paper, we present VM deflation as an alternative mechanism to server preemption for reclaiming resources from transient cloud servers under resource pressure. Using real traces from top-ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Summary. Prior work [4,14,43] did not consider the three major issues for production deployment of memory harvesting in real clouds: (1) The impact of memory harvesting on VM creation performance, (2) host memory fragmentation, and (3) NUMA spanning. Our work develops new techniques to address these challenges and improves existing techniques, such as the speed of runtime memory resizing, and develop new ones to mitigate these issues.…”
Section: Hypervisor-level Memory Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Summary. Prior work [4,14,43] did not consider the three major issues for production deployment of memory harvesting in real clouds: (1) The impact of memory harvesting on VM creation performance, (2) host memory fragmentation, and (3) NUMA spanning. Our work develops new techniques to address these challenges and improves existing techniques, such as the speed of runtime memory resizing, and develop new ones to mitigate these issues.…”
Section: Hypervisor-level Memory Managementmentioning
confidence: 99%
“…Second-level paging by the hypervisor to swap space or a remote server could be done to reclaim memory. [14] does this when cooperative memory trading cannot happen. However, cooperative memory trading on the same node involves less performance jitter (no I/O interrupts and no second-level page faults) and is much more efficient than paging to swap space or a remote node.…”
Section: Other Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulator CloudSim Plus [7,21] is used to present and simulate the scenarios to assess the proposed algorithm and methodology. For the simulation, a virtual host with a Virtual Machine setup matching the instances of Amazon T2.medium is used.…”
Section: Scenario-based Simulationmentioning
confidence: 99%
“…Resource deflation is a recently proposed approach for reclaiming resources by reducing the CPU and memory allocation of a virtual machine. The deflation approach proposed in [26,44] is based on the observation that virtual machines have slack in their resource allocation (since their allocated resources may not be 100% utilized by the application code executing inside them) and reclaiming a fraction of the VM's allocated resource can be done without a proportionate degradation in application performance. The deflation study in [26] has analyzed millions of production VMs in the Azure cloud and showed that typical slack can be up to 50%.…”
Section: Resource Reclamation Algorithmsmentioning
confidence: 99%